2001
DOI: 10.1021/ie0010520
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Liquid Membranes:  CO2 Separation from Gas Mixtures

Abstract: A generation 0 poly(amidoamine) (PAMAM) dendrimer in the immobilized liquid membrane (ILM) configuration was studied using flat films and hollow fibers for CO 2 -N 2 separation. This dendrimer as a pure liquid functions as a CO 2 -selective molecular gate with highly humidified feed gas (Kovvali et al. J. Am. Chem. Soc. 2000, 122, 7594). The present work broadens the range of relative humidity of the feed gas stream (RH f ) by adding a small amount of glycerol to the pure dendrimer liquid. A 75% dendrimer-25% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 30 publications
2
94
0
Order By: Relevance
“…Some liquid membranes using porous membranes containing dendrimers in the pores were reported. [34][35][36] A dendrimer membrane was prepared by the immersion of porous a hydrophilized polyvinylidene fluoride flat membrane (porosity 0.7; pore size 0.1 mm; thickness 100 mm; tortuosity 2.58; Millipore) into pure G0 PAMAM dendrimer or glycerol solution of G0 PAMAM dendrimer. 34,35 The CO 2 /N 2 permeation performance through the liquid membranes was measured under various humidity.…”
Section: Dendrimers Supported By Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some liquid membranes using porous membranes containing dendrimers in the pores were reported. [34][35][36] A dendrimer membrane was prepared by the immersion of porous a hydrophilized polyvinylidene fluoride flat membrane (porosity 0.7; pore size 0.1 mm; thickness 100 mm; tortuosity 2.58; Millipore) into pure G0 PAMAM dendrimer or glycerol solution of G0 PAMAM dendrimer. 34,35 The CO 2 /N 2 permeation performance through the liquid membranes was measured under various humidity.…”
Section: Dendrimers Supported By Membranesmentioning
confidence: 99%
“…[34][35][36] A dendrimer membrane was prepared by the immersion of porous a hydrophilized polyvinylidene fluoride flat membrane (porosity 0.7; pore size 0.1 mm; thickness 100 mm; tortuosity 2.58; Millipore) into pure G0 PAMAM dendrimer or glycerol solution of G0 PAMAM dendrimer. 34,35 The CO 2 /N 2 permeation performance through the liquid membranes was measured under various humidity. The separation factor CO 2 /N 2 was almost 19000 at a low CO 2 partial pres-sure (Áp CO 2 ¼ 0:36 cmHg) under the completely humidified condition, while it was around 700 at the higher Áp CO 2 (> 30 cmHg).…”
Section: Dendrimers Supported By Membranesmentioning
confidence: 99%
“…It was suggested that the permeance of CO 2 could be increased by increasing CO 2 carrier solubility in the ILM liquid and by preparing ILMs with thinner hydrophilic supports. In another study by the same authors [202,203], they used polyamidoamine (PAMAM) generation 0 dendrimers having ethylenediamine as the CO 2 carrier in porous hydrophilic polyvinyldine fluoride supported ILM. Dendrimer immobilized liquid membranes containing a high concentration of primary and tertiary amine provided a facilitated CO 2 transport and also nearly eliminated the other gases.…”
Section: Facilitated Transport Membranesmentioning
confidence: 99%
“…Various FTMs for CO2 capture have been developed and many efforts have been made to enhance the CO2 permeability and selectivity. The specific performances of the FTMs have been widely investigated and it was empirically determined that the CO2 permeability and selectivity of FTMs under humid conditions were quite high 4,6,8,9,11,12) . Especially, the CO2 permeabilities of the FTMs containing amino acid as the CO2 carrier were strongly affected by humidity in the gas stream 6,8) .…”
Section: Introductionmentioning
confidence: 99%